1997
DOI: 10.1021/jp971300e
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study on the Reaction of CHF3 with H at High Temperatures

Abstract: The reaction of CHF 3 (HFC-23) with H atoms has been investigated by using a shock tube-atomic resonance absorption spectroscopy technique over the temperature range 1100-1350 K and the total concentration range 5.5 × 10 18 -8.5 × 10 18 molecules cm -3 . Ethyl iodide was used as a precursor of hydrogen atoms. The rate coefficient for the reaction CHF 3 + H f CF 3 + H 2 (1a) was determined from the decay profiles of H-atom concentration to be k 1a ) 10 -9.80(0.10 exp [-(64.6 ( 2.3) kJ mol -1 /RT] cm 3 molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Details of the structure and the performance have been described previously [20]. The test section was evacuated by a turbomolecular pump to pressures down to 1 × 10 −4 Pa, in which the residual gas was practically free from hydrocarbons.…”
Section: Shock Tubementioning
confidence: 99%
“…Details of the structure and the performance have been described previously [20]. The test section was evacuated by a turbomolecular pump to pressures down to 1 × 10 −4 Pa, in which the residual gas was practically free from hydrocarbons.…”
Section: Shock Tubementioning
confidence: 99%
“…Berry et al 12 reported low level calculations using the G2(MP2) and the semiempirical BAC-MP4 approach to compute rate constants in the temperature range 298-2500 K for the reaction CHF 3 + H f products. Takahashi et al 9 performed G2(MP2) calculations adjusting the barriers to their experimental data in order to predict rate constants for all elementary reactions in the temperature range 1100-1350 K. More recently, Maity et al 13 6 In this work, highly correlated ab initio quantum chemical calculations were performed in order to directly compute the reaction barriers for the title reactions without any further adjustments of the energy. The energetics of these reactions was used together with TST calculations to compute rate constants in the temperature range 300-2500 K. For all of the reactions, all possible elementary pathways are computed and their relative importance under thermal oxidation and combustion conditions (700-2500 K) are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The details of its structure and its performance have been described previously. 1 The test section was evacuated by a turbomolecular pump to pressures down to 1 × 10 -6 Torr, in which the residual gas was practically free from hydrocarbons. To measure incident shock velocity, three piezoelectric pressure transducers were mounted on the shock tube walls at 25-cm intervals from the end of the test section.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, its inhibition mechanism is not yet known, due to the absence of kinetic data for high-temperature reactions in the fluorocarbon combustion. So, in an earlier paper, 1 we have reported the rate coefficient for the reaction CHF 3 + H f CF 3 + H 2 , which is an initial reaction in the CHF 3 combustion and one of the most important inhibition reactions. As the second part of our research on the flame suppression by CHF 3 , we focus on the high-temperature kinetics of the subsequent reactions of CF 3 radicals with some active species in the combustion.…”
Section: Introductionmentioning
confidence: 99%